Development of an interactive House Rental Information System (HRIS) prototype / Norizan Ismail - Ismail, Norizan (2006)
Owning a house can be very expensive. Therefore, the only alternative is to rent a house. Before having a house for rent, people have to find house by surveying if there any advertisement regarding rental house. To find a house for rent is absolutely not an easy task. This process usually is time consuming and tiring. Thus, the Interactive House Rental Information System (HRIS) prototype is developed in order to solve this problem. This web-based system is able to help potential house renter to find the available house by looking at the location on the interactive map. This system also provide mailbox for communication purpose between house renter and house owner. This project is developed for the house owner who have house for rent in Shah Alam and potential house renter who are intended to rent a house in Shah Alam. This prototype will give benefit to potential house renter in finding and renting house. Besides, the house owner will have a platform to advertise and rent out their house. Keyword: interactive map, mailbox